Mitigation of inorganic scaling in electrodialysis for desalination - Loh, Hua Ji (Nanyang Technological University, 2022)
The presence of scaling has been proven to be of a huge issue in the process of desalination processes, with divalent ions such as calcium and magnesium to be the major causes of scaling. This project looks to focus on the scaling aspects of electrodialysis where a novel ion exchange membrane that only allows monovalent ions to pass through to be used to mitigate scaling. The project seeks to observe the impacts of scaling in terms of energy consumption to prove the significant impacts of scaling, thereby comparing it to a setup that includes the monovalent ion exchange membrane. Experimental comparison between the setups was done through having closely similar setups in order to isolate the element of interest (energy consumption). Comparison for the significance of scaling on energy consumption was done through two different setups of different feedwater of sodium chloride as a baseline against a model seawater, with the sodium chloride feed being the baseline for energy consumption without scaling formation. Results for the comparison of baseline against model seawater concluded that there is a significant energy increase with the model seawater having a higher diluate salinity at a given voltage thus, showing the impact of scaling within the setup. A mass balance of calcium and magnesium was also conducted to show the presence of missing calcium and magnesium after the experiment, thus, proving that calcium and magnesium was lost through scaling. The comparison of the baseline with the monovalent ion exchange membrane setup resulted differently from the initial hypothesis, where the model seawater had a lower salinity than the baseline at a lower given voltage, but subsequently still had a higher salinity from a given voltage thus, showing an increase in resistance with higher voltages. The mass balance calculated showed that there was little loss in calcium and magnesium. Thus, it was concluded that the novel ion exchange membrane resulted as such due to other factors such as the degree of membrane deformation and bubble formation, between the baseline and monovalent ion exchange membrane during the experimental run. A bubble mitigated run was done where the outlet streams of the stack was placed in a way that it will hit the wall of the beaker before entering the respective bulk solutions in an effort to reduce the amount of bubbles present within the system. This was done as significant bubble formation was observed in the later parts of each experiment and was hypothesized to have a larger impact on the energy consumption. This resulted in a much closer voltage at a given diluate salinity between the baseline and model seawater solution for the monovalent ion exchange membrane setup. It proved the significant impact of bubbles on the stack resistance within the setup and consequently, the energy consumption. Even though the monovalent ion exchange membrane resulted in lower scaling formation, it did result in the divalent ions to be present within the diluate, thus sacrificing the purity of the product water.